Excel(lence) with interest - Walker, Russell (London : Kellogg School of Management, 2018)
James, a financial advisor at Bank Private, is advising a high net worth client with $1 million to invest. Bank Private can offer an investment that returns a fixed rate of 5.5% (compounded annually) for twenty years. James needs to prepare financial projections for the client that include annual interest and annual taxes as well as total interest and total taxes.
Originally Published InWalker, R. (2018). Excel(lence) With Interest. 5-217-256TN. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bank Private; Financial planners; Investment advisors; Affluent consumers -- Finance, Personal